Quality management models and health: a search for excellence (Research, Society and Development, 2020)
This study aimed to analyze the empirical investigations regarding the model of management excellence and its relevance to assess quality of health management. It is a narrative review of the literature carried out in the MEDLINE databases via PubMed®, Web of ScienceTM, Scopus (Elsevier), LILACS bibliographic index, SciELO electronic library and Google Scholar. 16 publications were selected and the location, the studied management model, the type of institution, methodological procedures and study outcomes were identified. The production addresses the theoretical aspects that support the management models, their application in different types of institutions and the contribution of the model adopted in the management and results improvement. It was concluded that the search for quality in health institutions promotes efficiency, efficacy and effectiveness. The studies point out the benefits of adopting the management model, such as improvements in processes and products, cost reduction, expansion of the degree of management maturity, increased productivity and better conditions to achieve and maintain the desired performance.